(untitled) (AYUSHDHARA, 2024)
Psoriasis is a chronic inflammatory and hyper proliferative skin disease. It is characterized by well-defined, erythematous scaly papules affecting about 0.1% to 3% of the population. Psoriasis can be correlated to Ekakushta which is Kapha-vata predominant. It presents with Aswedana, Mahavasthu and Matsya Shakalopama and is treated with Shodhana Karma and Bahya Chikista including Lepa Karma that occupies the prime place in its line of treatment. Acharyas have mentioned different types of Lepas and its effectiveness in skin disorders. Objective of study: To study the effect of Jeevantyadi Lepa and Vidangadi Lepa in Ekakushta and to compare its therapeutic effects in the management of Ekakushta w.s.r. to psoriasis Methods: This is a comparative clinical study with pre-test and post-test design that included 40 patients of either sex diagnosed as Ekakusta (psoriasis). All the 40 patients were randomly assigned into 2 groups with 20 patients in each. The procedure in group A involves application of Vidangadi Lepa and group B involves application of Jeevantyadi Lepa. Results: The overall results in the study revealed the statistically significant results in Group A and in Group B on all subjective and objective parameters. Conclusions: Group A and Group B had shown significant results but however Group A had an edge over to Group B.